Low Cost Mechanical Prosthetic Hand (Metic Hand) Design For Under Elbow Hand Amputation Patients - Yasya Khalif Perdana Saleh; Rifky Ismail; Mochammad Ariyanto (ROTASI, 2022)
Hands are one part of the human body that has an important role in human daily activities. A lot of people have experienced hand disabilities in Indonesia, which is 158,000 per year. This can reduce an individual's quality due to limitations in carrying out activities. So as to help bring prosperity to the people of Indonesia by giving them tools that can support their lives. The purpose of this design task is to make a mechanical hand-made product that is affordable to all Indonesians by providing a low price product. The step of making this product is doing a product selection from mechanical prosthetic hands based on the design method that is identifying customer needs, technical specifications, concept alternatives, concept selection, selected concepts, selected concept analysis, prototyping, product printing, product testing, and product evaluation. Based on the results of the process, a mechanical prosthetic hand is obtained on the alternative concept 2, which will then be tested with consumers. That mechanical prosthetic hand was tested at Mas Muhammad Andika with the result of the movement of taking a tissue, taking food, lifting a bottle, moving a bucket, and lifting a bag. From the results of the tests carried out that there is an evaluation that can be developed on the product that the width of the grip is too narrow, which is 4 cm, so that it is only limited in the size of the grip, it is necessary to develop the second alternative hand model.